Engineering a bifunctional Phr60-Rap60-Spo0A quorum-sensing molecular switch for dynamic fine-tuning of menaquinone-7 synthesis in bacillus subtilis - Cui,S; Lv,X; Wu,Y; Li,J; Du,G; Ledesma-Amaro,R; Liu,L (ACS Synthetic Biology, 2019)
Quorum sensing (QS)-based dynamic regulation has been widely used as basic tool for fine-tuning gene expression in response to cell density changes without adding expensive inducers. However, most reported QS systems primarily relied on down-regulation rather than up-regulation of gene expression, significantly limiting its potential as a molecular switch to control metabolic flux. To solve this challenge, we developed a bifunctional and modular Phr60-Rap60-Spo0A QS system, based on two native promoters, P abrB (down-regulation by Spo0A-P) and P spoiiA (up-regulation by Spo0A-P). We constructed a library of promoters with different capacities to implement down-regulation and up-regulation by changing the location, number, and sequences of the binding sites for Spo0A-P. The QS system can dynamically balance the relationship between efficient synthesis of the target product and cell growth. Finally, we validated the usefulness of this strategy by dynamic control of menaquinone-7 (MK-7) synthesis in Bacillus subtilis 168, a model Gram-positive bacterium, with the bifunctional Phr60-Rap60-Spo0A quorum sensing system. Our dynamic pathway regulation led to a 40-fold improvement of MK-7 production from 9 to 360 mg/L in shake flasks and 200 mg/L in 15-L bioreactor. Taken together, our bilayer QS system has been successfully integrated with biocatalytic functions to achieve dynamic pathway regulation in B. subtilis 168, which may be extended for use in other microbes to fine-tune gene expression and improve metabolites production.